HCV genotype 3 and squamous cell carcinoma antigen (SCCA)‐IgM are independently associated with histological features of NASH in HCV‐infected patients. Issue 10 (22nd January 2015) - Martini, A.; Fattovich, G.; Guido, M.; Bugianesi, E.; Biasiolo, A.; Ieluzzi, D.; Gallotta, A.; Fassina, G.; Merkel, C.; Gatta, A.; Negro, F.; Pontisso, P.
Summary Nonalcoholic steatohepatitis (NASH) enhances the risk of progressive liver disease. In chronic hepatitis C (CHC), liver steatosis is frequent, especially in genotype 3, but its clinical significance is debated. As squamous cell carcinoma antigen (SCCA)‐IgM has been associated with advanced liver disease and risk of tumour development, we evaluated its occurrence in CHC and the possible relation with NASH at liver biopsy. Using a validated ELISA, serum SCCA‐IgM was measured in 91 patients with CHC at the time of liver biopsy performed before antiviral treatment, at the end of treatment and 6 months thereafter, and in 93 HCV‐negative patients with histological diagnosis of nonalcoholic fatty liver disease, as controls. SCCA‐IgM was detected in 33% of CHC patients and in 4% of controls. This biomarker was found more elevated in CHC patients with histological NASH, and at multivariate analysis, SCCA‐IgM and HCV genotype 3 were independently associated with NASH [OR (95% CI): 6.94 (1.21–40) and 27.02 (4.44–166.6)]. As predictors of NASH, HCV genotype 3 and SCCA‐IgM had a specificity and a sensitivity of 97% and 44%, and of 95% and 27%, respectively. PPV and NPV were 80% and 86% for HCV genotype 3 vs 73% and 72% for SCCA‐IgM. In patients with sustained virologic response to therapy, SCCA‐IgM levels decreased significantly, while these remained unchanged in nonresponders. In conclusion, SCCA‐IgM is detectable in one‐third of patients with CHC and significantly correlates with histological NASH.